The Effect Of Work Facilities, Work Motivation and Leadership Style on The Performance of Employees at The Tanjung Karang Religious Court Office - Praptiwi, Silvia; Amalya, Wulan Rezky (Universitas Pamulang, 2025)
This study aims to analyze the influence of work facilities, work motivation and leadership style partially and simultaneously on employee performance and analyze the most dominant variables that influence employee performance at the Tanjung Karang Religious Court. The research method is a survey. Data collection techniques by collecting data from questionnaires and documentation. Researchers distributed questionnaires within the Tanjung Karang Religious Court with a total of 50 respondents. The type of data used is primary data. Hypothesis testing in this study includes reliability testing, validity testing, multiple regression analysis testing, t-test (partial), and F-test (Simultaneous) with the help of SPSS version 26. Research Results from the calculation of the t-test(partial) it can be concluded that the Work Facilities variable (X1) has no positive effect, Work Motivation (X2) has a positive effect, and Leadership Style (X3) has no positive effect. While the F Test (Simultaneous) Partially Work Facilities, Work Motivation and Leadership Style together have a positive effect on the performance of Tanjung Karang Religious Court employees.